Honoring Día de los Muertos as a Mexican American Music Therapist: Individual and Community-Based Experiences - de León, Marisa (Voices: A World Forum for Music Therapy, 2024)
Día de los Muertos plays a significant role in Mexican American culture and has implications for how communities in the borderlands process experiences of death and dying. This article will describe the socio-historical context of this annual celebration, outline recommendations for establishing a community ofrenda in music therapy programs, and discuss culturally informed music experiences for individual and community-based music therapy treatment.